(untitled) (Journal of Human Sciences, 2021)
it is imperative for those who want to be saved in this world by following the divine approach in all the affairs of this world hereafter, and to follow the example of the greatest messenger, peace and blessings be upon him, and take the prophet’s biography reflects and contemplates that it is the right divine approach that our master, the messenger of god, may god bless him and grant him peace, lived in practically in all the affairs of his life. the teachings have the right guidance and the best examples for all to follow such as politics, economy. finance, social issues, international relationship, etc. fairly, muslims today have descended into the abyss of ignorance and backwardness. to move away from this approach - to return to their senses and present the biography in their all issues of their life.